Beszállítói kapcsolatok és az ipari együttműködés lehetséges klaszterei a Közép-Dunántúlon - Dőry, Tibor (Tér és Társadalom, 1998)
Nowadays, the issue of networks of suppliers and industrial cooperation is given a special attention. So far, in the fields of regional economics and spatial planning in Hungary, there has been no attempt to analyse the structures of zones of innovation, the complex processes of modern industrial change and the territorial aspects of flexible production systems within any Hungarian region. The article tries to address this challenge, on the one hand by applying some of the modern theories of economics and on other hand by analysing the empirical data of my interviews with company leaders in the Mid-Transdanubian region. These interviews were conducted for the purpose of setting up a complex regional development plan for the above-mentioned region. The analysis of networks of suppliers and industrial cooperation in Hungary after 1989, the comparison with European Union practises and the experiences of the companies in the region together may actively contribute to the improvement of networks of industrial cooperation. Ön the basis of theoretical investígation on the structures of networks of suppliers and industrial cooperation and the results of my empirical research, it should be noted that to catalyse regional development in any region, there needs to be existing a multilevel, developed and wide-ranging web of supplier networks and industrial cooperations. As a result of our research, we would like to conclude that it is necessary to set up various chambers and alliances of companies which participate or will participate in the regional networks of suppliers and industrial cooperations. These alliances and chambers should cooperate in building up new alliances between various economic actors, creating innovation strategies for regional development, producing and passing on information concerning different companies in the given region and in organising professional trainings and courses on the basis of the needs of the regional actors.